O que a política industrial pode aprender com a política monetária? - Schapiro, Mario Gomes (2013)
A number of evidence suggests a renewing of national states' interest in acting upon their economies. In Brazil, three new industrial policies were implemented starting in 2003, in addition to the regulatory policies introduced in the 1990s. This poses a challenge of institutional design: how to establish regulatory apparatuses which are economically responsive and densely institutionalized? Understanding the successes of monetary policy might help the elaboration of other economic policies, such as industrial policies. The result of this learning process might translate into credibility and legitimacy gains.